Group Behavior in Educational Institutions - Devi, Indra; Ilmi, Darul; Syafitri, Aisyah; Syamsurizal, Syamsurizal; Yakub Simbolon, Ali Mustopa (GIC Proceeding, 2023)
Group behavior in educational institutions is an important aspect in the formation of an effective and harmonious learning environment. The study of group behavior aims to understand how individuals interact, influence each other, and work together in an educational context. This study aims to analyze group behavior in educational institutions, including the factors that influence it and the consequences it has on students' academic achievement and social development. In carrying out this research, qualitative methods and literature studies or Library Research were used. Reviewing literature books in accordance with the theories discussed especially in the scope of Human Resource Management (HRM). The results of the study show that group behavior in educational institutions is influenced by factors such as social norms, group identity, group structure, and the role of individuals in groups. Positive group behaviors, such as collaboration, mutual support, and effective communication, have a positive impact on students' academic achievement and the development of their social skills, whereas negative group behaviors, such as bullying, unfair competition, and social exclusion, can interfere learning environment and student welfare.In an effort to improve group behavior in educational institutions, several practical implications can be drawn.It is necessary to develop educational programs that focus on building social skills, conflict resolution, and effective group management.In addition, it is also important to involve teachers and school staff in creating an inclusive environment and supporting positive group behavior. In conclusion, group behavior in educational institutions has an important role in forming an effective and harmonious learning environment. A good understanding of the factors influencing group behavior can assist in designing effective educational strategies to enhance students' academic achievement and social development.